PSYCHOSOCIAL MEDIATORS BETWEEN SOCIOECONOMIC STATUS AND PHYSICAL ACTIVITY IN OLDER JAPANESE ADULTS - Sugisawa, H. (Innov Aging, 2017)
Empirical studies conducted in developed countries have indicated differences in physical activities among older adults according to their socioeconomic status (SES). However, few studies have examined the mediators between SES and physical activity, and therefore, limited knowledge is available regarding the relation between SES and physical activity. This study examined the psychological mediators between SES and physical activities among older Japanese adults. Data were obtained from a probability sample survey conducted with 739 participants living in two wards of Tokyo, Japan. Physical activity was divided into active (engaged in 60 min or more per week) and inactive (not engaged in 60 min or more per week). SES was evaluated by educational attainment and household income. The following three dimensions of psychological mediators were assessed: control expectancy for physical activity, self-efficacy of physical activity, and social support for physical activity. Age, sex, and daily activities were included as control variables. A multiple mediator model was used to evaluate the indirect effects of SES through the mediators. Educational attainment was found to influence physical activity significantly. In addition, the relation between educational attainment and physical activity was mediated by two mediate variables: self-efficacy and social support; in particular, self-efficacy had the strongest mediating effect. These two significant variables explained the majority of differences in physical activity resulting from different educational attainment levels. Household income did not influence on physical activity significantly. Therefore, it is necessary to enhance self-efficacy and social support to promote healthy physical activities among SES-disadvantaged older adults in Japan.